Ultrasonic transducers radiating into the air in the frequency range 50-250 kHz - PAJEWSKI, M.; SZALEWSKI, M. (Archives of Acoustics, 1992)
In the paper ultrasonic piezoelectric transducers radiating into the air in the frequency range 50-250 kHz are described. Methods of improving their properties (efficiency, frequency characteristics, directivity characteristics) are discussed. Several types of designed, made and investigated transducers are presented. The transducers have the form of properly shaped piezoelectric plates or an array of plates embedded in plastic. The properties of these transducers enable their application in robotics, e.g., in echolocation or in object identification systems.